Relational morality in psychology and philosophy: past, present, and future - Earp, BD; Calcott, R; Reinecke, MG; Everett, JAC (Edward Elgar Publishing, 2024)
Moral psychology research often frames participant judgments in terms of adherence to abstract principles, such as utilitarianism or Kant's categorical imperative, and focuses on hypothetical interactions between strangers. However, real-world moral judgments typically involve concrete evaluations of known individuals within specific social relationships. Acknowledging this, a growing number of moral psychologists are shifting their focus to the study of moral judgment in social-relational contexts. This chapter provides an overview of recent work in this area, highlighting strengths and weaknesses, and describes a new 'relational norms' model of moral judgment developed by the authors and colleagues. The discussion is situated within influential philosophical theories of human morality that emphasize relational context, and suggests that these theories should receive more attention from moral psychologists. The chapter concludes by exploring future applications of relational-moral frameworks, such as modeling and predicting norms and judgments related to human-AI cooperation.